2011
DOI: 10.3892/ol.2011.285
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of anti-apoptotic transmembrane protein lifeguard sensitizes solid tumor cell lines MCF-7 and SW872 to perifosine-induced cell death activation

Abstract: Abstract. Lifeguard (LFG), an anti-apoptotic protein with high expression rates in breast cancer cells, has been identified as a molecule that inhibits death mediated by Fas. The molecular function of LFG and its regulation in the carcinogenesis of human breast and sarcoma cells, however, remains to be elucidated. In the present study, we investigated the ability of LFG expression to inhibit apoptosis induced by the alkylphospholipid perifosine. Results showed that LFG was able to be downregulated in selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A year later, the same authors reported that FAIM2 down‐regulation enhanced sensitivity to an agonistic Fas antibody and to perifosine, an alkylphospholipid that induces apoptosis by inhibiting the AKT and phosphatidylinositol 3‐kinase pathway (Bucan et al . ). Recent studies described a new isoform of FAIM2, named FAIM2β, which lacks one of the transmembrane domains.…”
Section: Faim2mentioning
confidence: 97%
See 2 more Smart Citations
“…A year later, the same authors reported that FAIM2 down‐regulation enhanced sensitivity to an agonistic Fas antibody and to perifosine, an alkylphospholipid that induces apoptosis by inhibiting the AKT and phosphatidylinositol 3‐kinase pathway (Bucan et al . ). Recent studies described a new isoform of FAIM2, named FAIM2β, which lacks one of the transmembrane domains.…”
Section: Faim2mentioning
confidence: 97%
“…These data allowed them to hypothesize that FAIM2 participates in protecting breast cancer cells from apoptosis, conferring on them a more aggressive phenotype (Bucan et al 2010b). A year later, the same authors reported that FAIM2 down-regulation enhanced sensitivity to an agonistic Fas antibody and to perifosine, an alkylphospholipid that induces apoptosis by inhibiting the AKT and phosphatidylinositol 3-kinase pathway (Bucan et al 2011). Recent studies described a new isoform of FAIM2, named FAIM2b, which lacks one of the transmembrane domains.…”
Section: Faim2mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous publications, it has been demonstrated that there is a correlation between the expression level of LFG and the increasing degree of malignity of breast cancer ( 5 ). Furthermore, it was shown that the effect of the alkyl phospholipid perifosine was reduced in cells expressing LFG ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that a decreased sensitivity to FasL-induced apoptosis is based on a high LFG mRNA and protein expression rate, which was notably discovered in breast cancer cell lines. LFG downregulation therefore implicates an attractive therapeutic chance for anticancer therapy via antisense oligonucleotides or siRNA [21][22][23]. While the exact molecular mechanism of LFG regulation has not yet been fully understood, it is hypothesized as mediated by the PI3-K/Akt/LEF-1 signalling pathway because PI3-K/Akt inhibition in MCF-7 and MDA-MB-231 breast cancer cells leads to increased rates of apoptosis and reduced amounts of LFG mRNA and Protein [23,24].…”
Section: Introductionmentioning
confidence: 99%